‘Stupid Girls’ vs. ‘Real Men’: Identity Construction and Social Media Polarization over Revenge Porn - Marta Sánchez Cócera (Revista Alicantina de Estudios Ingleses)
The purpose of this paper is to explore polarization in the discourse of social media commentators over crimes of Revenge Porn. Revenge porn refers to “the nonconsensual sharing of intimate images” (Bond and Tyrrell 2021, 2166), videos, or other intimate material, which are weaponized against its victims. As with other crimes, revenge porn cases are highly discussed on social media, where users might (a) reproduce prejudice and stigma against victims or, contrarily, (b) resist victim-blaming and shaming ideologies as a form of activism and call for empathy (Garcés-Conejos Blitvich and Bou-Franch 2019; Palomino-Manjón 2022). In light of this, this paper examines the discursive construction of the phenomenon of revenge porn and the evaluations proposed of victims and perpetrators on the social network YouTube with the aim of unveiling conflicting ideologies online. To this end, the present study analyzes a corpus of 14,000 comments (ca. 411,000 words) from four different YouTube videos tackling revenge porn cases. The paper adopts a Corpus-Assisted Discourse Studies (CADS) approach (Partington et al. 2013) and uses Sketch Engine to analyze the corpus. Additionally, a more detailed analysis of evaluative resources and linguistic patterns is carried out. Results show that polarized understandings of revenge porn abound in the corpus. Specifically, victim-blaming ideologies are discursively concealed, whereas traditional ideologies regarding sex are overtly encoded. Moreover, male users affiliate with newer constructions of masculinity and dissociate from the illegal actions attributed to perpetrators. Women/victims are generally derogated for not conforming to societal views of common-sensical sexual behavior or praised for their strength in standing social judgment.